In silico reversal of repeat-induced point mutation (RIP) identifies the origins of repeat families and uncovers obscured duplicated genes. - Hane, J.; Oliver, Richard (Biomed Central, 2010)
Background: Repeat-induced point mutation (RIP) is a fungal genome defence mechanism guarding against transposon invasion. RIP mutates the sequence of repeated DNA and over time renders the affected regions unrecognisable by similarity search tools such as BLAST. Results: DeRIP is a new software tool developed to predict the original sequence of a RIP-mutated region prior to the occurrence of RIP. In this study, we apply deRIP to the genome of the wheat pathogen Stagonospora nodorumSN15 and predict the origin of several previously uncharacterised classes of repetitive DNA. Conclusions: Five new classes of transposon repeats and four classes of endogenous gene repeats were identified after deRIP. The deRIP process is a new tool for fungal genomics that facilitates the identification and understanding of the role and origin of fungal repetitive DNA.